Optimasi Rute Pengiriman Capacitated Vehicle Routing Problem with Time Windows PT. X - Widi Santoso Wijanarko; Nova Sepadyati (Jurnal Titra, 2022)
Optimization in the distribution process needs to be done to increase the efficiency and effectiveness of delivery, reduce travel distance, and save costs. One of the optimization processes in the distribution process is to determine the optimal distribution route. Route optimization will help a company with a lot of customer combination that need to be served everyday with a limited resources or constraints. The purpose of this research is to help PT. X to have a reference for making the optimal route in solving the capacitated vehicle routing problem with time windows. AnyLogistix Software will be used in the optimization process to determine the optimal distribution route by building a model inside the software with capacitated vehicle and time windows constraints. Optimization’s results shows more than 20% distance reduction that can be used to determine retail product delivery routes based on measurable data for PT. X